ANALISIS RESEPSI KONTEN SOFT SELLING BERBENTUK PARODI PADA PRODUK TENUE DE ATTIRE DI TIKTOK - Pehulisa, Karin; Ratri Rahmiaji, Lintang; Surayya Ulfa, Nurist (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This study examines audience reception of soft selling content in the form of parody for the local fashion brand Tenue de Attire on TikTok. Although intended as promotional content, the audience primarily perceives it as parody, as reflected in their comments. Using qualitative methods and reception analysis based on Stuart Hall's Theory of Reception and Peirce's Semiotics, the research involves in-depth interviews with four male TikTok users. Of the four respondents, two are in the Negotiated Position, initially seeing the content as a parody but recognizing elements of soft selling. One is in the Dominant Position, fully interpreting the content as entertaining parody, while one is in the Opposition Position, viewing it entirely as a soft selling marketing strategy. The study concludes that audience interpretation is influenced by their background and preferences